Bis coumarinyl bis triazolothiadiazinyl ethane derivatives: Synthesis, antiviral activity evaluation, and molecular docking studies. Issue 12 (18th June 2018) - Pavurala, Sreenu; Vaarla, Krishnaiah; Kesharwani, Rajeshkumar; Naesens, Lieve; Liekens, Sandra; Vedula, Rajeswar Rao
ABSTRACT: A series of novel 3, 3′-(3, 3′-(dihydroxy/hydroxyethane-1, 2-diyl)bis(7 H -[1, 2, 4]triazolo[3, 4- b ][1, 3, 4]thiadiazine-6, 3-diyl))bis(2 H -chromen-2-ones) were prepared by the condensation of thiocarbohydrazide with tartaric acid or malic acid followed by various 3-(2-bromoacetyl)-2 H -chromen-2-ones in two steps with good yields. All the synthesized compounds were characterized by analytical and spectral (IR, 1 H NMR, 13 C NMR, and mass) data. These synthesized bis(triazolothiadiazinyl coumarin) compounds were evaluated for broad spectrum of antiviral activity. Among all the tested compounds, compound5f exhibited antiviral activity against H1N1 virus. The molecular docking studies of these compounds against H1N1 neuraminidase enzyme were performed. The binding affinity and binding values were compared with standard drugs. GRAPHICAL ABSTRACT: